Creep behaviour of dense and porous SrTi0.75Fe0.25O3-δ for oxygen transport membranes and substrates. Issue 15 (December 2018) - Oliveira Silva, R.; Malzbender, J.; Schulze-Küppers, F.; Baumann, S.; Krüger, M.; Guillon, O.
Abstract: Considering the challenging conditions imposed by application of membranes in an asymmetric design, in particular creep resistance of the substrate material is an important parameter for the stability in long-term operation. As promising material, in terms of chemical stability, the perovskite SrTi0.75 Fe0.25 O3-δ has been identified in previous works. Porous supports with different microstructures have been produced using different manufacturing methods and compared to the material in its fully dense state regarding creep behaviour. The creep deformation of pressed, porous tape-cast and freeze-dried SrTi0.75 Fe0.25 O3-δ specimens has been investigated in the application relevant temperature range of 850–1000 °C under compressive stresses of 15, 30 and 45 MPa. A global fitting method considering all experimental data was used to derive stress exponent and activation energy of SrTi0.75 Fe0.25 O3-δ, which are 2.9 ± 0.4 and 402 ± 25 kJ/mol, respectively. Thus, it is suggested that the mechanism controlling creep is mainly related to dislocation climb/glide.